2019
DOI: 10.12944/crnfsj.7.2.22
|View full text |Cite
|
Sign up to set email alerts
|

Extraction, Purification, and Characterization of Lycopene from Jordanian Vine Tomato Cultivar, and Study of its Potential Natural Antioxidant Effect on Samen Baladi

Abstract: Lycopene is one of the carotenoids, a fat-soluble pigment that has antioxidant properties. Lycopene was extracted from vine tomato wastes, characterized and then introduced to Jordanian traditional sheep ghee (Samen Baladi). The quality attributes in term of peroxide value PV, acidity (%FFA), refractive index (RI) and iodine value (IV) were analyzed according to reference methods. CIE C*.H*. L* colour is measured using Konika Minolta CR-400 Chroma Meter handheld. All parameters were analyzed after storage for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Crude lycopene extraction was performed and determined according to the method described by Ranganna [ 27 ] and Mai et al [ 28 ]. Lycopene content was calculated using Equation (4).…”
Section: Methodsmentioning
confidence: 99%
“…Crude lycopene extraction was performed and determined according to the method described by Ranganna [ 27 ] and Mai et al [ 28 ]. Lycopene content was calculated using Equation (4).…”
Section: Methodsmentioning
confidence: 99%
“…The enriched butter’s storage conditions remained stable, which was a result of the enhanced antioxidant activity. Another study was conducted in order to evaluate the employment of lycopene in Jordanian traditional sheep butter as a natural antioxidant agent [ 104 ]. The results displayed lycopene’s positive impact concerning the stabilization of butter recipes.…”
Section: Food Applicationsmentioning
confidence: 99%
“…The storage stability (during 60 days of storage at 4 °C) of the enriched butter was clearly increased due to the strong antioxidant activity that inhibited the formation of peroxide and conjugated dienes, as well as the breakdown of unsaturated fatty acids into oxidation products. In a similar study, the potential use of lycopene as a natural antioxidant added to Jordanian traditional sheep butter was demonstrated [ 99 ]. The overall results showed that natural lycopene may have a role in stabilizing the butter formulations, along with the benefit of adding a functional nutrient into such product.…”
Section: Applications In the Food Industrymentioning
confidence: 99%